2012
DOI: 10.1007/s10068-012-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Clarification, preservation, and shelf life evaluation of cashew apple juice

Abstract: Cashew apples are tropical fruits rich in sugars, minerals, and vitamin C. In spite of having high nutritional value, neither the fresh cashew apples nor the juice is consumed due to astringency. In the present investigation an attempt was made to reduce the astringency without affecting the nutrient quality of the juice. The clarifying agent, sago at a concentration of 2 g/L, has decreased the tannins by 42.85% but the respective sample's visual clarity is only 94%. The same clarifying agent with the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 18 publications
3
66
1
7
Order By: Relevance
“…Crisp et al, (2007) compared both pH and Brix on juice between powdery mildew fungicide treated and untreated grape fruits and found no significant differences. Our study is in line with Ough and Bug (1979) and McFadden-Smith and Pickering (2006) because Brix in fruit juices reflects the maturity of source fruits and thus good palatability and acceptance (Godoury et al, 2001;Talasila et al 2011). Therefore, cashew powdery mildew increase on apples surface leads to improved quality of juice and respective wine by increasing Brix.…”
Section: Powdery Mildew Effect On Total Soluble Solids (Tss)supporting
confidence: 88%
See 2 more Smart Citations
“…Crisp et al, (2007) compared both pH and Brix on juice between powdery mildew fungicide treated and untreated grape fruits and found no significant differences. Our study is in line with Ough and Bug (1979) and McFadden-Smith and Pickering (2006) because Brix in fruit juices reflects the maturity of source fruits and thus good palatability and acceptance (Godoury et al, 2001;Talasila et al 2011). Therefore, cashew powdery mildew increase on apples surface leads to improved quality of juice and respective wine by increasing Brix.…”
Section: Powdery Mildew Effect On Total Soluble Solids (Tss)supporting
confidence: 88%
“…However, lower value, 70 mg/100ml was reported by Awe et al, (2013) but no association is made with powdery mildew occurrence in all studies above. Our findings are much higher than 80.91 to 121 mg/100ml found in Brazilian cashew juice (Costa et al, 2003;Deenanath et al, 2013) but falls in the range between 164.00-164.67 mg/100 ml reported by Talasila et al, (2011) in India. This variation may be due to variations in climatic growing conditions, fruit harvesting stage and conservation conditions in association with ascorbinase enzyme activity (Ferrã o, 1995).…”
Section: Powdery Mildew Effect On Vitamin C Contentcontrasting
confidence: 67%
See 1 more Smart Citation
“…Many studies also reported enzymes based clarification of four kinds of fruits juices, i.e., tangerine, orange, grapefruit and apple (Lu et al, 2009).Sensory qualities of apple juice have also been reported to be improved with the help of enzymes (Joshi and Bhutani, 1991;Joshi et al, 2011). Clarification, of cashew apple juice and evaluation of its sensory attributes in terms of color, flavor, taste, sedimentation, and overall acceptability have been reported (Talasila et al, 2012). Recent studies also reported sensory attributes, such as color, aroma, taste, and overall acceptance for various seed juices (Park et al, 2017).…”
Section: Overall Acceptability Ratingmentioning
confidence: 99%
“…Clarification was carried out on a tubular microfiltration module using polyethersulfone membranes (0.3 µm pore size and 0.05 m 2 of permeation area). Some chemicals such as tannase and polyvinyl pyrolidone are expensive and not readily available, and microfiltration is difficult to operate (Talasila et al, 2012).…”
Section: Introductionmentioning
confidence: 99%